2014
DOI: 10.1111/cbdd.12394
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Antidepressant‐like Activity of Some 4‐Substituted 1‐(2‐methoxyphenyl)Piperazine Derivatives

Abstract: A series of new derivatives of N-(2-methoxyphenyl)piperazine have been synthesized for their affinity toward serotonergic receptors and for their potential antidepressant-like activity. They have been evaluated toward receptors 5-HT1A , 5-HT6 , and 5-HT7 , as well as in vivo in the tail suspension, locomotor activity, and motor co-ordination tests. All the tested compounds proved very good affinities toward 5-HT1A and 5-HT7 receptors. The most promising compound was 1-[(2-chloro-6-methylphenoxy)ethoxyethyl]-4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 18 publications
4
47
0
Order By: Relevance
“…HBK-14 and HBK-15 possessed significant antidepressant-like properties after acute treatment (Waszkielewicz et al 2015; Pytka et al 2015a). Both compounds showed α 1 -adrenolytic properties, and only HBK-15 did not lower blood pressure at antidepressant-like doses after single administration (Pytka et al 2016b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HBK-14 and HBK-15 possessed significant antidepressant-like properties after acute treatment (Waszkielewicz et al 2015; Pytka et al 2015a). Both compounds showed α 1 -adrenolytic properties, and only HBK-15 did not lower blood pressure at antidepressant-like doses after single administration (Pytka et al 2016b).…”
Section: Discussionmentioning
confidence: 99%
“…1): 1-[(2,6-dimethylphenoxy)ethoxyethyl]-4-(2-methoxyphenyl)piperazine hydrochloride (HBK-14) and 1-[(2-chloro-6-methylphenoxy)ethoxyethyl]-4-(2-methoxyphenyl)piperazine hydrochloride (HBK-15) were synthesized in the Department of Bioorganic Chemistry, Chair of Organic Chemistry, Pharmaceutical Faculty, Jagiellonian University (Waszkielewicz et al 2015). HBK-14, HBK-15, and scopolamine (Sigma, Germany) were dissolved in saline, and administered intraperitoneally (i.p.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studied compounds (Fig 1): 1-[(2,6-dimethylphenoxy)ethoxyethyl]-4-(2-methoxyphenyl)piperazine hydrochloride (HBK-14) and 1-[(2-chloro-6-methylphenoxy)ethoxyethyl]-4-(2-methoxyphenyl)piperazine hydrochloride (HBK-15) were synthesized in the Department of Bioorganic Chemistry, Chair of Organic Chemistry, Faculty of Pharmacy, Jagiellonian University [10]. HBK-14, HBK-15, terazosin and thiopental (Rotexmedica, Germany) were dissolved in saline and administered intraperitoneally (i.p.).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have suggested that the 5-HT 1A -Rs are potential targets for these psychiatric disorders [45][46][47][48][49]. In this regard, agonists (total and partial) to the 5-HT 1A -R have shown antidepressant and anxiolytic properties and have been employed as adjunct treatments to improve the therapeutic action of several antidepressant and anxiolytic drugs in several preclinical and clinical studies [50][51][52][53]. They offer a different pharmacological mechanism from that of the monoamine oxidase inhibitors (IMAO), tricyclic drugs, SSIRs, and other antidepressants.…”
Section: Therapeutic Agents That Function By Regulating 5-ht 1a -R Simentioning
confidence: 99%